The Legal Nature and the Effects of Privatization of Public Companies in Iranian Law - Pour, Sajjad Ghasem; Mohammad, Abasat Pour (Management in Dialogue Review, 2017)
According to recent challenges in the past years and worries of the authorities in handing over the public sectors to the private sectors,we tried to study the legal and issues in this research which have studied the general policies of code 44, the sector of legal empowerment in terms of the assignment and legal loopholes in this regard,the type and weakness of assignment in terms of legal that was studied generally not partly with the aim of interpretation of the law by the authorities and the absence of known solutions and common law provisions on the right of states and as well as assignment and assignment as the shares via the stock and OTC, Face- to-face negotiation and not to transfer the ownership.